Pemberlakuan Izin Pengisian Bahan Bakar di Free Trade Zone Batam oleh PT. Pelayaran Nasional Nusantara Perkasa - Rini Tarigan; Dafid Ginting; Yusnidah Yusnidah (Jurnal Pemimpin Bisnis Inovatif, 2025)
The purpose of this paper is to understand the implementation of the Fuel Filling Permit system in the Tax-Free Zone at PT. Pelayaran Nasional Nusantara Perkasa. This paper analyzes the implementation of the Fuel Filling Permit using a fleet of tankers and ships in the Free Trade Zone (FTZ), specifically in the Free Trade Zone and Free Port (KPBPB) such as Batam. The implementation of this permit is closely related to the regulations on fuel distribution and management, which are regulated by the government and area management bodies such as the Batam Free Trade Zone Authority (BP Batam). PT. Pelayaran Nasional Nusantara Perkasa is an official fuel filling agent for PT. Pertamina Patra Niaga in Batam, which will fill fuel or provide fuel for ships. This research method utilizes field and library methods. The results of this study provide the company with a better understanding of the procedures for obtaining a Fuel Filling Permit using a fleet of tankers and ships in the Free Trade Zone (TFZ), which can be submitted online and directly to the relevant agency office.